Legal Protection Of Heirs Testamenter To Testament Agreement Which Not Registered (Case Study Testamenter Without Heirs) - Amalia Putri Prima Erdian; Hulman Siregar; Arief Cholil (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Law of inheritance only happens because the person died. In BW there are two ways to get wealth, that is: as heirs according to the provisions of law and as a person appointed in the will. What is meant by the will itself according to Article 875 BW is an agreement that make statements about what he wished someone would happen after he died, and that by her to pull back. In general, people make a will before a Public Notary. According to article 1 paragraph 1 of Act No. 2 of 2014 concerning On Notary (now referred to UUJN). Notary is a public official who is authorized to make authentic agreements and other authorities referred to in the Act, where each testament must be shaped agreement in order to obtain certainty law as an authentic agreement binding. With the creation of the will meant that the parties can understand and be able to know the basic result of the offense can be arranged so that the interests of the concerned receive proper protection as known by the Notary.Keywords: Inheritance; Heir; Testament; Authentic Agreement